The signal transduction of xanthone as a protector on 2-methoxyethanol-induced cardiac cell damage in mice - Ernawati; Reny I'tishom; Sri Agus Sudjarwo (Wolters Kluwer Medknow Publications, 2019)
This research aims at investigating the role of antioxidant of xanthone on 2-methoxyethanol (2-ME)-induced cardiac cell damage in mice. Forty mice were grouped into: (1) The control group (mice were given with distilled water), (2) the ME group (mice were given with 2-ME 200 mg/kg BW orally), and (3) the treatment group (mice were given of xanthone with doses 60 mg, 120 mg, 240 mg/kg BW orally and were also given 2-ME 200 mg/kg BW). Their blood samples were taken to measure the level of lactate dehydrogenase (LDH) and creatinine kinase-MB (CK-MB). Heart tissues were also taken to determine the malondialdehyde (MDA), histological findings of heart damage, and the immunohistochemical of the expression of superoxide dismutase (SOD) and glutathione peroxidase (GPx). The administration of 2-ME resulted in a significant increase level of the LDH, CK-MB, MDA, and a decrease in SOD and GPx expression were compared with the control group. The 2-ME also induced loss of the normal structure of heart cells and necrosis. However, treatment with the xanthone, only dose 240 mg/kg BW significantly decrease the level of LDH, CK-MB, MDA, and increase SOD, GPx expression. The xanthone 240 mg/kg BW also demonstrated significantly improved heart cell damage. From the results, it is concluded that the xanthone are a potent antioxidant in against 2-ME-induced cardiac toxicity in mice, through increasing SOD and GPx expression, and also inhibiting LDH, CK-MB and MDA.